A ascens\~ao naval Chinesa e as disputas territoriais marítimas no leste asiatico - Rodrigo Fracalossi de Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The paper aims to analyze the relations between the disputes over maritime territories in East Asia, the unfavorable maritime situation of China, and the Chinese military build-up from the early 1990s onwards. From the data collected, it indicates the aspects that make China a country with an unfavorable maritime situation. It also indicates the main features of China's military modernization (particularly in the Navy) and of the maritime territorial disputes in East Asia. It follows that it has occurred in China, especially since the early 2000s, a significant modernization of the national military power, along with a higher priority assigned to naval power. Although sea denial capabilities are still prevalent, there are evidences indicating the development of a power projection navy. Evidences indicate, moreover, a rapid redistribution of military power in East Asia in favor of China, expanding the possibilities of success of a Chinese military action in that space. Furthermore, superiority of China is most evident in the South China Sea, in which military presence of the United States is weaker and where countries have less resources when compared to countries in the East China Sea.
Keywords: F51; 330; China; armed forces; naval power; maritime disputes; East Asia